Gambaran Self Esteem pada Mahasiswa yang Mengalami Kekerasan dalam Pacaran di Universitas Jambi - Aldino Gustriansyah; Dessy Pramudiani; Agung Iranda (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
This study aimed to describe self esteem among students experiencing dating violence at Universitas Jambi. Dating violence is a common phenomenon in emerging adulthood and may negatively affect psychological well-being, including decreased self-confidence, feelings of worthlessness, and emotional dependence on a partner. This study used a qualitative method with a phenomenological approach. The participants were three female students aged 18–25 years who had experienced dating violence. Data were collected through in-depth interviews, observation, and documentation, then analyzed using Interpretative Phenomenological Analysis. The findings showed that participants experienced various forms of violence, including verbal, emotional, physical, and sexual violence. These experiences affected their self esteem, which was reflected in feelings of fear, self-blame, low self-worth, loss of confidence, and difficulty leaving unhealthy relationships. In addition, self esteem was influenced by environmental factors, previous relationship experiences, parenting patterns, and social support. The study concludes that dating violence has a significant impact on the psychological condition of victims, particularly on the development of self esteem during emerging adulthood.